Diuretic Effect and Metabolomics Analysis of Crude and Salt-Processed Plantaginis Semen - Li, Chao; Wen, Rou; Liu, De Wen; Liu, Qiang; Yan, Li Ping; Wu, Jian Xiong; Guo, Yi Jing; Li, Su Yun; Gong, Qian Feng; Yu, Huan (Frontiers in Pharmacology, 2020)
Plantaginis semen (PS) is well recognized in traditional Chinese medicine (TCM) and health products. Crude PS (CPS) and saline-processed PS (SPS) are the two most common commercial forms of PS. In this study, we employed a combination of pharmacological methods and metabolomics in saline-loaded rats to investigate the diuretic effect of CPS and SPS ethanol extracts and the potential mechanism involved in this process. The results showed that CPS and SPS both produced increased urine volume excretion and urine electrolyte excretion, but the levels of aldosterone (ALD) and aquaporin 2 (AQP2) were decreased. And 30 differential metabolites were found, mainly involving 3 metabolic pathways. In conclusion, CPS and SPS both have a diuretic effect, and that of SPS is better. This work investigated the possible diuretic mechanism of CPS and SPS and provided novel and valuable insight into the interpretation of the processing mechanisms of TCM in a holistic way.